2012
DOI: 10.1016/j.jfi.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Loan officers and relationship lending to SMEs

Abstract: Previous research suggests that loan officers play a critical role in relationship lending by producing soft information about SMEs. For the first time, we empirically confirm this hypothesis We also examine whether the role of loan officers differs from small to large banks as predicted by Stein (2002). While we find that small banks produce more soft information, the capacity and manner in which loan officers produce soft information does not seem to differ between large and small banks. This suggests that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(112 citation statements)
references
References 56 publications
5
103
0
4
Order By: Relevance
“…The greater the loan officer's experience and the most frequent the loan officer-entrepreneur relationship, the more accurate soft information he/she will produce. Uchida, Yamori, and Udell (2012) found that the production of soft information increases with skill level of loan officer (e.g., loan officer turnover, loan officer age) and loan officer lending activities (e.g., frequency of meeting and method of contact). In recent study, loan officer turnover is introduced as a potentially better proxy of the quality of soft information produced than length of banking relationship.…”
Section: Predictive Accuracy Of Soft Information and Strength Of Lendmentioning
confidence: 99%
“…The greater the loan officer's experience and the most frequent the loan officer-entrepreneur relationship, the more accurate soft information he/she will produce. Uchida, Yamori, and Udell (2012) found that the production of soft information increases with skill level of loan officer (e.g., loan officer turnover, loan officer age) and loan officer lending activities (e.g., frequency of meeting and method of contact). In recent study, loan officer turnover is introduced as a potentially better proxy of the quality of soft information produced than length of banking relationship.…”
Section: Predictive Accuracy Of Soft Information and Strength Of Lendmentioning
confidence: 99%
“…(unverifiable) information can be collected and updated through a long-term lending relationship (Petersen and Rajan, 1994;Berger and Udell, 1995;Uchida, Udell and Yamori, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the banks sought to encourage the SMEs to use more transparent ways of reporting their business operations, bringing them into the 'public domain' (Jackson et al, 2008), to reduce the SMEs' reliance on indigenous, tacit knowledge. The banks extensively used relationship lending where loan officers collected soft information to help inform lending decisions, and mitigate the firms' opacity (Sahar & Anis, 2016;Uchida et al, 2012). This approach was combined with transaction-based lending (based on contracts, proformas, and evidence of legal business operations).…”
Section: Case Backgroundmentioning
confidence: 99%
“…Although soft information can be more suitable for assessing SMEs, it can deteriorate over time as it passes through the bank's communication hierarchy (Uchida et al, 2012).…”
Section: Case Backgroundmentioning
confidence: 99%